- 1-800-665-6601
- [email protected]

In order to prove the above given trigonometric identity, we have to first start by picking any side of the equation.

Here let’s start with the left-hand side of the equation->cot(θ)/cosec(θ)

We can also write the above expression as: cot(θ)/cosec(θ) = [cos(θ)/sin(θ)]/ [1/sin(θ)]

Now taking the reciprocal we get->[cos(θ)/sin(θ)] * [sin(θ)/1]

Now, sin(θ) gets cancelled, and we get ->cos(θ) = right-hand side of the equation!

Hence proved!

In order to prove the above given trigonometric identity, we have to first start by picking any side of the equation.

Here let’s start with the left-hand side of the equation ->sec(θ) * cot(θ)

We can also write the above expression as: sec(θ) * cot(θ) = [1/cos(θ)] * [cos(θ)/sin(θ)]

Here the cos(θ) present in the numerator and the denominator gets cancelled and we get ->[1/sin(θ)] .

This implies: 1/sin(θ) = cosec(θ) = right-hand side of the equation!

Hence proved!